Impulsive Functional-Abstract Neutral Functional Differential Nonlocal Cauchy Problem with State-dependent Delay - Karthikeyan, K.; Nieto, J.J. (Discontinuity, Nonlinearity, and Complexity, 2026)
We study existence,uniqueness and continuous dependence of a mild solution for an impulsive neutral functional differential nonlocal Cauchy problem with state- dependent delay in general Banach spaces are studied by using the fixed point technique and semigroup of operators.